2019
DOI: 10.1108/yc-10-2018-0867
|View full text |Cite
|
Sign up to set email alerts
|

Materialist values, financial and pro-environmental behaviors, and well-being

Abstract: Purpose The purpose of this study is to examine young consumers’ financial behavior (e.g. saving) and pro-environmental behavior (i.e. reduced consumption and green buying) as effective proactive strategies undertaken in the present to satisfy materialistic values and maximize well-being. Design/methodology/approach The study is based on an online survey among a panel of young American adults (N = 968). Findings The study finds a positive effect of materialism on personal well-being and negative effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 85 publications
0
52
1
3
Order By: Relevance
“…There has been a growing interest in the investigation of responsible financial behavior of young adults (Pinto et al , 2000; Watson, 2003; Norvilitis et al , 2006; Yang et al , 2008; Tang et al , 2015; Bamforth et al , 2018; Bapat, 2020). Efficient and well-structured financial decisions, hence responsible financial behavior, is crucial for young people’s prosperity in personal and professional life (Sachitra et al , 2019), as well as in the advance of general well-being (Helm, et al , 2019). Therefore, it is necessary to investigate young adults’ financial behavior to better understand and predict their financial behavior but also to encourage responsible and avoid irresponsible financial behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing interest in the investigation of responsible financial behavior of young adults (Pinto et al , 2000; Watson, 2003; Norvilitis et al , 2006; Yang et al , 2008; Tang et al , 2015; Bamforth et al , 2018; Bapat, 2020). Efficient and well-structured financial decisions, hence responsible financial behavior, is crucial for young people’s prosperity in personal and professional life (Sachitra et al , 2019), as well as in the advance of general well-being (Helm, et al , 2019). Therefore, it is necessary to investigate young adults’ financial behavior to better understand and predict their financial behavior but also to encourage responsible and avoid irresponsible financial behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Another example shows a negative effect of materialism on FWB for young consumers, but a positive relationship on personal well-being, a finding that needs further investigation for broader consumer samples (Helm et al, 2019). In a more recent study, Strömbäck et al (2017) found that self-control as an individual difference parameter significantly predicts positive financial behavior such as savings and financial anxiety (which is a measure of FWB).…”
Section: Cross-country Research In Fwbmentioning
confidence: 97%
“…Another example shows a negative effect of materialism on FWB for young consumers, but a positive relationship on personal well‐being, a finding that needs further investigation for broader consumer samples (Helm et al., 2019). In a more recent study, Strömbäck et al.…”
Section: An Organizing Framework Of Research Gaps In Financial Well‐beingmentioning
confidence: 99%
“…Thus, society in general and green consumers, in particular, are questioning the genuineness of green marketing activities, particularly after the Volkswagen scandal in 2015. In addition, research has demonstrated that "green buying", in reality, offers a way for materialists to fulfill their desire to accumulate new items [51]. For this reason, green marketing appears as a pretense alternative for continued consumption to satisfy the extrinsic goals of individual consumers or to have recognition from other stakeholders [52].…”
Section: A Proposed Framework For Sustainability Level In Marketingmentioning
confidence: 99%